Epidemiological review and clinicopathological study of gastric adenocarcinoma cases in a tertiary care center in North Chennai, India - Padmavathi, R.; Priyadharisini, J. (International Journal of Research in Medical Sciences, 2019)
Background: Gastric carcinoma is the third most common cause of cancer-related mortality worldwide. The Incidence of gastric carcinoma shows wide geographic and regional variation as well. The clinical presentation varies with the individual and hence histopathological evaluation plays a major role in the diagnosis and management of the patients. This study aims to evaluate the epidemiological and clinicopathological profile of gastric adenocarcinoma cases encountered in a tertiary care center in North Chennai where only limited statistical data available in literature. Methods: All the gastric adenocarcinoma cases diagnosed by histopathology who underwent total/subtotal gastrectomy were retrospectively collected for clinical as well as histopathological details for a year. Descriptive statistics were used for analysis. Results: The mean age of the study population is 59.3±11.3 with male: female sex ratio of 2.1:1. Higher prevalence noted in lower socioeconomic status (80%) and alcoholics (65%) with a history of high salted diet (62%). Most common presenting symptom was dyspepsia (94%). Upper GI endoscopy revealed antrum (42%) as the commonest site of tumor and majority were more than 5 cm size (75%). 62% of tumors were of moderately differentiated, predominantly intestinal type (86%) and mostly found to be in stage 3 (50%). Conclusions: Gastric adenocarcinoma was more common in elderly males and majority presented in advanced stage at the time of diagnosis. The General public needs to be creating awareness about variable nonspecific symptoms of an early stage of gastric carcinoma as well as the risk of poor dietary habits (high salted diet) and can enforce screening of high-risk category people.